Preparation method of cerium oxide-based electrolyte powder containing sintering aid
By using compounds containing carboxyl, hydroxyl, and amino groups to complex with sintering aids in cerium oxide-based electrolyte powder, the problem of uneven mixing of sintering aids in cerium oxide-based electrolyte powder was solved, achieving uniform dispersion of aids and improved battery performance.
Patent Information
- Application Number
- CN202511185201.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-12-02
AI Technical Summary
When adding sintering aids to cerium oxide-based electrolyte powder, uneven mixing leads to uneven sintering, which affects battery performance.
Compounds containing carboxyl, hydroxyl, and amino groups are mixed with sintering aids and cerium oxide-based electrolyte raw powder. The sintering aids are uniformly dispersed on the surface of the cerium oxide-based electrolyte powder through a complexation reaction. Combined with ball milling and drying steps, the aids are ensured to be uniformly coated.
This method achieves uniform dispersion of sintering aids in cerium oxide-based electrolyte powder, reduces sintering temperature, improves battery electrical performance and density, and avoids performance degradation caused by uneven mixing.
Smart Images

Figure CN121054752A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy technology, and in particular to a method for preparing cerium oxide-based electrolyte powder containing sintering aids. Background Technology
[0002] Solid oxide fuel cells (SOFCs) are power generation devices that directly convert chemical energy into electrical energy. A single cell typically consists of three parts: a porous anode and cathode, and a dense electrolyte layer. The most commonly used anode material is Ni-3YSZ metal, while the cathode often uses a 10GDC-LSCF composite cathode. The dense electrolyte material in between is usually a zirconium-based electrolyte (such as 8YSZ or 1Ce-ScSC). Because SOFCs require high-temperature sintering during fabrication, Sr in the cathode LSCF reacts with Zr in the zirconium-based electrolyte, producing a Zr-Sr phase with low ionic conductivity, significantly reducing the electrical performance of the SOFC. Therefore, a barrier layer is usually added to the original three-layer structure (anode-electrolyte-cathode), forming a four-layer structure (anode-electrolyte-barrier layer-cathode) to prevent the reaction between Sr in the cathode and Zr in the electrolyte.
[0003] Cerium oxide-based electrolytes possess high ionic conductivity, stability under high-temperature oxidizing atmospheres, and do not react with Sr at the cathode, making them the preferred material for the barrier layer. However, Ce in cerium oxide-based electrolytes can also react with Zr in the electrolyte material above 1200℃, forming a phase with low ionic conductivity, thus affecting the electrical performance of SOFC single cells. Therefore, to avoid the reaction between Ce and Zr, the preparation temperature of the barrier layer must be below 1200℃.
[0004] Generally, the sintering temperature of cerium oxide-based electrolyte materials (such as GDC or SDC materials) prepared by liquid-phase methods is greater than 1400℃, which obviously does not meet the requirement of being below 1200℃ in the single-cell fabrication process. Therefore, in practical applications, sintering aids are usually added to the cerium oxide-based electrolyte powder to lower its sintering temperature to below 1200℃.
[0005] Currently, the main method for adding sintering aids to cerium oxide-based electrolyte powder is wet ball milling. However, there is a problem that the sintering aids are not mixed evenly in the cerium oxide-based electrolyte material, resulting in uneven sintering and affecting the quality of the cerium oxide-based electrolyte powder. Summary of the Invention
[0006] This application provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, in order to solve the problem of uneven sintering caused by uneven mixing of sintering aids in cerium oxide-based electrolyte materials.
[0007] In a first aspect, this application provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, comprising the following steps: The sintering aid and solvent are mixed to obtain the first mixture; The first mixture is mixed with a complexing agent and a dispersant to obtain a second mixture; The second mixture is mixed with cerium oxide-based electrolyte powder to obtain a third mixture. The third mixture is ball-milled, dried, and sintered to obtain cerium oxide-based electrolyte powder containing sintering aids. The complexing agent includes compounds containing carboxyl, hydroxyl, and amino groups.
[0008] The dispersant includes hexadecyltrimethylammonium bromide.
[0009] This application adds compounds containing carboxyl, hydroxyl, and amino groups. A portion of these compounds complexes with sintering aid metal ions that are self-soluble in the solvent, while another portion complexes with active sites on the surface of the electrolyte powder. This allows the carboxyl, hydroxyl, and amino groups to complex with the sintering aid when the first mixture is mixed with the complexing agent. When the second mixture is mixed with cerium oxide-based electrolyte powder, the carboxyl, hydroxyl, and amino groups in the compound can further complex with active sites on the surface of the cerium oxide-based electrolyte powder (such as surface hydroxyl groups and surface cerium ions), thereby fixing the sintering aid to the surface of the cerium oxide-based electrolyte powder. Since the compound containing carboxyl, hydroxyl, and amino groups is uniformly dispersed in the solution, when mixed with the cerium oxide-based electrolyte powder, the complexing agent, which has complexed with the sintering aid, can also uniformly complex the cerium oxide-based electrolyte powder, thus achieving uniform dispersion of the sintering aid in the cerium oxide-based electrolyte powder.
[0010] It should be noted that cerium oxide-based electrolyte raw material refers to cerium oxide-doped powder. This can be gadolinium oxide-doped cerium oxide or samarium oxide-doped cerium oxide, etc.
[0011] In some embodiments, the compounds containing carboxyl, hydroxyl, and amino groups include citric acid, glycine, etc. By selecting at least one of the above compounds, the carboxyl, hydroxyl, and amino groups and the sintering aid can form a complex. When the second mixture is mixed with the cerium oxide-based electrolyte powder, the carboxyl, hydroxyl, and amino groups in the compounds containing these groups can further complex with the active sites (such as surface hydroxyl groups, surface cerium ions, etc.) on the surface of the cerium oxide-based electrolyte powder.
[0012] In some embodiments, the complexing agent includes at least one of glycine and citric acid. Using at least one of the above compounds allows for complexation with compounds containing carboxyl, hydroxyl, or amino groups.
[0013] In some embodiments, the molar ratio of sintering aid to complexing agent is 1:(3~5). Within this range, the molar ratio of sintering aid to complexing agent ensures complete complexation of the sintering aid while reserving sufficient complexation sites to complex with the active sites on the cerium oxide-based electrolyte powder, thus achieving uniform dispersion of the sintering aid.
[0014] In some embodiments, the mass percentage of cerium oxide-based electrolyte powder in the third mixture is 20% to 60%. This mass percentage range ensures that the cerium oxide-based electrolyte powder is fully immersed in the solvent and mixed with the sintering aid, while avoiding excessive liquid that could affect ball milling.
[0015] In some embodiments, the mass ratio of dispersant to solvent in the third mixture is (1~5):100. Within this range, the dispersant can be evenly distributed throughout the solution system, thereby improving the dispersibility of the powder and avoiding the adverse effects on the subsequent ball milling process caused by excessive dispersant altering the properties of the solvent.
[0016] In some embodiments, the molar ratio of the sintering aid to the cerium oxide-based electrolyte powder is 1:(80~200). This molar ratio can reduce the sintering temperature of the cerium oxide-based electrolyte powder and decrease impurities, thus minimizing their impact on battery performance.
[0017] In some embodiments, the sintering aid includes at least one selected from iron salts, bismuth salts, cobalt salts, and copper salts, such as ferric nitrate, copper nitrate, and bismuth nitrate. Using at least one of these sintering aids makes it easier for the sintering aid to undergo complexation reactions with compounds containing carboxyl, hydroxyl, or amino groups; and / or, The solvent includes deionized water.
[0018] In some embodiments, the ball milling speed is 300~500 r / min. Within this range, the ball milling speed can effectively break up agglomerates of cerium oxide-based powders, thereby allowing the sintering aid to be uniformly coated on the powder surface; and / or, The ball milling time is 6–48 hours. Within this range, the agglomeration of cerium oxide-based powder is completely broken up, while allowing sufficient time for sintering aids and complexing agents to coat the surface of the cerium oxide-based nanoparticles; and / or, The drying temperature is 120~180℃. Within this range, the solvent can be effectively removed, ensuring the powder is completely dried; and / or, The drying time is 6 to 24 hours. Within this range, sufficient time is allowed for the solvent to evaporate completely.
[0019] In some embodiments, the sintering temperature is 550~650℃. Within this range, the organic matter in the powder can be effectively removed without leaving carbon deposits; and / or, The sintering time is 1 to 3 hours. Within this range, sufficient time is allowed to remove organic matter from the powder without leaving carbon deposits. Attached Figure Description
[0020] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0021] Figure 1 The image shows the XRD pattern of the cerium oxide-based electrolyte powder containing sintering aids from Example 1 of this application.
[0022] Figure 2 The images are SEM images of the cerium oxide-based electrolyte powder containing sintering aids before and after ball milling in Example 1 of this application.
[0023] Figure 3 This is a conductivity diagram of the cerium oxide-based electrolyte powder containing sintering aids in Example 1 of this application. Detailed Implementation
[0024] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0025] Solid oxide fuel cells (SOFCs) are power generation devices that directly convert chemical energy into electrical energy. A single cell typically consists of three parts: a porous anode and cathode, and a dense electrolyte layer. The most commonly used anode material is Ni-3YSZ metal, while the cathode often uses a 10GDC-LSCF composite cathode. The dense electrolyte material in between is usually a zirconium-based electrolyte (such as 8YSZ or 1Ce-ScSC). Because SOFCs require high-temperature sintering during fabrication, Sr in the cathode LSCF reacts with Zr in the zirconium-based electrolyte, producing a Zr-Sr phase with low ionic conductivity, significantly reducing the electrical performance of the SOFC. Therefore, a barrier layer is usually added to the original three-layer structure (anode-electrolyte-cathode), forming a four-layer structure (anode-electrolyte-barrier layer-cathode) to prevent the reaction between Sr in the cathode and Zr in the electrolyte.
[0026] Cerium oxide-based electrolytes possess high ionic conductivity, stability under high-temperature oxidizing atmospheres, and do not react with Sr at the cathode, making them the preferred material for the barrier layer. However, Ce in cerium oxide-based electrolytes can also react with Zr in the electrolyte material above 1200℃, forming a phase with low ionic conductivity, thus affecting the electrical performance of SOFC single cells. Therefore, to avoid the reaction between Ce and Zr, the preparation temperature of the barrier layer must be below 1200℃.
[0027] Generally, the sintering temperature of cerium oxide-based electrolyte materials (such as GDC or SDC materials) prepared by liquid-phase methods is greater than 1400℃, which obviously does not meet the requirement of being below 1200℃ in the single-cell fabrication process. Therefore, in practical applications, sintering aids are usually added to the cerium oxide-based electrolyte powder to lower its sintering temperature to below 1200℃.
[0028] Currently, the main method for adding sintering aids to cerium oxide-based electrolyte powders is wet ball milling. Taking the addition of iron oxide as a sintering aid to 10GDC powder as an example, there are two common methods: 1. Selecting iron oxide as the iron source, wet ball milling is used to uniformly mix the iron oxide powder and cerium oxide-based electrolyte powder, followed by drying to obtain 10GDC powder with added iron oxide; 2. Selecting ferric nitrate as the iron source, ferric nitrate can dissolve in the ball milling media, thus coating the surface of the powder during the subsequent drying process, and further calcination is used to obtain a composite powder of iron oxide-10GDC. For the first method, since the amount of sintering aid added is usually only about 1 mol% of the total molar amount of the powder, and due to the huge difference in mass and volume between the two powders, it is actually difficult to achieve uniform mixing by direct ball milling. The second mixing method uses soluble ferric nitrate as the iron source. Although theoretically, the liquid phase can be uniformly coated on the surface of GDC powder to obtain a uniformly mixed Fe-GDC composite powder, drying is a process that often takes a period of time to complete. During this period, the nanoparticles are prone to agglomeration and sedimentation, which leads to the separation of the powder and liquid. As a result, a large number of Fe ions contained in the upper clear liquid cannot be coated on the surface of the GDC powder.
[0029] In view of this, this application provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, in order to solve the problem of uneven sintering caused by uneven mixing of sintering aids in cerium oxide-based electrolyte materials.
[0030] In a first aspect, this application provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, comprising the following steps: The sintering aid and solvent are mixed to obtain the first mixture; The first mixture is mixed with a complexing agent and a dispersant to obtain a second mixture; The second mixture is mixed with cerium oxide-based electrolyte powder to obtain a third mixture. The third mixture is ball-milled, dried, and sintered to obtain cerium oxide-based electrolyte powder containing sintering aids. The complexing agent includes compounds containing carboxyl, hydroxyl, and amino groups.
[0031] This application adds compounds containing carboxyl, hydroxyl, and amino groups. A portion of these compounds complexes with sintering aid metal ions that are self-soluble in the solvent, while another portion complexes with active sites on the surface of the electrolyte powder. This allows the carboxyl, hydroxyl, and amino groups to complex with the sintering aid when the first mixture is mixed with the complexing agent. When the second mixture is mixed with cerium oxide-based electrolyte powder, the carboxyl, hydroxyl, and amino groups in the compound can further complex with active sites on the surface of the cerium oxide-based electrolyte powder (such as surface hydroxyl groups and surface cerium ions), thereby fixing the sintering aid to the surface of the cerium oxide-based electrolyte powder. Since the compound containing carboxyl, hydroxyl, and amino groups is uniformly dispersed in the solution, when mixed with the cerium oxide-based electrolyte powder, the complexing agent, which has complexed with the sintering aid, can also uniformly complex the cerium oxide-based electrolyte powder, thus achieving uniform dispersion of the sintering aid in the cerium oxide-based electrolyte powder.
[0032] This application enables the metal ions in the sintering aid, which were originally free in the solution, to tightly complex onto the surface of the electrolyte powder. On the other hand, it can also effectively prevent the agglomeration and sedimentation of the nanoparticles, so that the sintering aid does not separate from the powder during the drying process. Ultimately, the sintering aid can be uniformly coated on the surface of the cerium oxide-based electrolyte powder after calcination.
[0033] It should be noted that cerium oxide-based electrolyte raw material refers to cerium oxide-doped powder. This can be gadolinium oxide-doped cerium oxide powder or samarium oxide-doped cerium oxide powder. The cerium oxide-based electrolyte raw material can be a commercially available product or homemade. A method for homemade cerium oxide-based electrolyte raw material is as follows: Using cerium nitrate, gadolinium nitrate (Ga), or samarium nitrate (Sm) as raw materials and deionized water as solvent, prepare a cerium nitrate-gadolinium nitrate or samarium nitrate mixed mother salt solution with a cerium ion to gadolinium ion or samarium ion molar ratio of 9:1. Stir to obtain a clear mother salt solution A. Using ammonium bicarbonate as a precipitant and deionized water as a solvent, prepare an ammonium bicarbonate solution with a molar volume 2.5 times that of the metal ions as a precipitant solution B. Slowly add mother salt solution A dropwise to precipitant solution B, stirring continuously during the addition process. After the addition was completed, the solid and liquid in the solution were immediately separated using a high-speed centrifuge. The centrifuged product was then washed three times with deionized water and anhydrous ethanol. Finally, the washed powder was placed in an oven and dried at 80°C for 12 hours to obtain powder C. Powder C was then placed in a muffle furnace and annealed at 600°C for 2 hours to obtain the described nano-cerium oxide-based electrolyte powder.
[0034] In conjunction with the first aspect, in some embodiments provided in this application, the compounds containing carboxyl, hydroxyl, and amino groups include citric acid and glycine. By selecting at least one of the above compounds, the carboxyl, hydroxyl, and amino groups and the sintering aid can form a complex. When the second mixture is mixed with the cerium oxide-based electrolyte powder, the carboxyl, hydroxyl, and amino groups in the compounds containing these groups can further complex with the active sites (such as surface hydroxyl groups, surface cerium ions, etc.) on the surface of the cerium oxide-based electrolyte powder.
[0035] In conjunction with the first aspect, in some embodiments provided in this application, the complexing agent includes at least one of glycine and citric acid. Using at least one of the above compounds allows for complexation with compounds containing carboxyl, hydroxyl, or amino groups.
[0036] In conjunction with the first aspect, in some embodiments provided in this application, the molar ratio of sintering aid to complexing agent is 1:(3~5). Within this range, the molar ratio of sintering aid to complexing agent ensures complete complexation of the sintering aid while reserving sufficient complexation sites to complex with the active sites on the cerium oxide-based electrolyte powder, thereby achieving uniform dispersion of the sintering aid.
[0037] In conjunction with the first aspect, in some embodiments provided in this application, the mass percentage of cerium oxide-based electrolyte powder in the third mixture is 20% to 60%. Maintaining this mass percentage ensures that the cerium oxide-based electrolyte powder is fully immersed in the solvent and mixed with the sintering aid, while avoiding excessive liquid volume that could affect ball milling.
[0038] In conjunction with the first aspect, in some embodiments provided in this application, the mass ratio of dispersant to solvent in the third mixture is (1~5):100. This mass ratio of dispersant to solvent, within this range, allows the dispersant to be uniformly distributed throughout the solution system, thereby improving the dispersibility of the powder. It also avoids the adverse effects on the subsequent ball milling process caused by excessive dispersant altering the properties of the solvent.
[0039] In conjunction with the first aspect, in some embodiments provided in this application, the molar ratio of the sintering aid to the cerium oxide-based electrolyte powder is 1:(80~200). This molar ratio of sintering aid to cerium oxide-based electrolyte powder, within this range, can both reduce the sintering temperature of the cerium oxide-based electrolyte powder and reduce impurities, thus minimizing the impact on battery performance.
[0040] In conjunction with the first aspect, in some embodiments provided in this application, the sintering aid includes at least one of iron salts, bismuth salts, cobalt salts, and copper salts, such as ferric nitrate, copper nitrate, and bismuth nitrate. Using at least one of the above-mentioned sintering aids makes it easier for the sintering aid to undergo complexation reactions with compounds containing carboxyl, hydroxyl, and amino groups.
[0041] In conjunction with the first aspect, in some embodiments provided in this application, the solvent is deionized water.
[0042] In conjunction with the first aspect, in some embodiments provided in this application, the ball milling speed is 300~500 r / min. Within this range, the ball milling speed can effectively break up the agglomeration of cerium oxide-based powder, thereby allowing the sintering aid to be uniformly coated on the powder surface.
[0043] In conjunction with the first aspect, in some embodiments provided in this application, the ball milling time is 6 to 48 hours. Within this range, the agglomeration of cerium oxide-based powder can be completely broken up, while giving the sintering aid and complexing agent sufficient time to coat the surface of the cerium oxide-based nanoparticles.
[0044] In conjunction with the first aspect, in some embodiments provided in this application, the drying temperature is 120~180°C. The drying temperature within this range can effectively remove the solvent, so that the powder is completely dried.
[0045] In conjunction with the first aspect, in some embodiments provided in this application, the drying time is 6 to 24 hours. This drying time range allows sufficient time for the solvent to completely evaporate.
[0046] In conjunction with the first aspect, in some embodiments provided in this application, the sintering temperature is 550~650℃. Within this range, the organic matter in the powder can be effectively removed without leaving carbon deposits.
[0047] In conjunction with the first aspect, in some embodiments provided in this application, the sintering time is 1 to 3 hours. Within this range, the sintering time allows sufficient time to remove organic matter from the powder without leaving carbon deposits.
[0048] The technical solution provided in this application will be described in detail below with reference to embodiments. The method for preparing the self-made cerium oxide-based electrolyte powder can be as follows: using cerium nitrate, gadolinium nitrate (Ga), or samarium nitrate (Sm) as raw materials and deionized water as solvent, a mixed mother salt solution of cerium nitrate-gadolinium nitrate or samarium nitrate is prepared according to a molar ratio of cerium ions to gadolinium ions or samarium ions of 9:1. The solution is stirred to obtain a clear mother salt solution A. Using ammonium bicarbonate as a precipitant and deionized water as a solvent, a solution of ammonium bicarbonate with a molar amount 2.5 times that of the metal ions is prepared as a precipitant solution B. Mother salt solution A is slowly added dropwise to precipitant solution B, with continuous stirring during the addition process. After the addition is complete, the solid and liquid in the solution are immediately separated using a high-speed centrifuge. The centrifuged product is then washed three times with deionized water and anhydrous ethanol. Finally, the washed powder is placed in an oven and dried at 80°C for 12 hours to obtain powder C. Powder C is placed in a muffle furnace and annealed at 600°C for 2 hours to obtain the described nano-cerium oxide-based electrolyte powder.
[0049] Example 1 Example 1 of this application provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, comprising the following steps: Calculate the mass of sintering aid (ferric nitrate), complexing agent (citric acid, glycine), dispersant (hexadecyltrimethylammonium bromide), cerium oxide electrolyte powder, and solvent (deionized water), respectively. The solid content of the cerium oxide-based electrolyte powder is 50%wt (i.e., the mass ratio of cerium oxide-based electrolyte powder to solvent deionized water = 1:1). The amount of sintering aid (ferric nitrate) added is 1%mol of cerium oxide-based electrolyte powder (i.e., the molar ratio of cerium oxide-based electrolyte powder to sintering aid is 100:1). The molar ratio of complexing agent (glycine, citric acid) to sintering aid is 4:1, of which the molar ratio of glycine to citric acid is 1:1. The amount of dispersant (hexadecyltrimethylammonium bromide) added is 5%wt of the mass of the solvent deionized water (i.e., the mass ratio of dispersant to solvent = 1:20). The sintering aid (ferric nitrate) was added to the solvent water, and the ferric nitrate was completely dissolved in the water at 80°C to obtain the first mixture. The complexing agent (citric acid, glycine) and the dispersant (hexadecyltrimethylammonium bromide) were added to the first mixture and mixed evenly at 80°C to obtain the second mixture. The second mixture is mixed with cerium oxide-based electrolyte powder to obtain a third mixture. The third mixture is ball-milled at 350 r / min for 24 h, dried at 150 °C for 6 h, and sintered at 600 °C for 2 h to obtain cerium oxide-based electrolyte powder containing sintering aid.
[0050] Examples 2-5 Examples 2-5 of this application provide a method for preparing cerium oxide-based electrolyte powder containing sintering aids. The only difference between the method and Example 1 is the solid content of the cerium oxide-based electrolyte powder, as shown in Table 1.
[0051] Table 1. Solid content of oxide-based electrolyte powders in Examples 2-5
[0052] Examples 6-9 Examples 6-9 of this application provide a method for preparing cerium oxide-based electrolyte powder containing sintering aids. The only difference between this method and Example 1 is the amount of hexadecyltrimethylammonium bromide added as a dispersant, as shown in Table 2.
[0053] Table 2. Amount of dispersant (hexadecyltrimethylammonium bromide) added in Examples 6-9
[0054] Examples 10-13 Examples 10-13 of this application provide a method for preparing cerium oxide-based electrolyte powder containing sintering aids. The only difference between this method and Example 1 is the amount of sintering aids added, as shown in Table 3.
[0055] Table 3. Amounts of sintering aids added in Examples 10-13
[0056] Examples 14-16 Examples 14-16 of this application provide a method for preparing cerium oxide-based electrolyte powder containing sintering aids. The only difference between this method and Example 1 is the sintering aid, as shown in Table 4.
[0057] Table 4. Types of sintering aids in Examples 14-16
[0058] Examples 17-20 This application 17-20 provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, which differs from Example 1 only in the drying temperature, as shown in Table 5.
[0059] Table 5. Drying temperatures in Example 17
[0060] Comparative Example 1 Comparative Example 1 of this application provides a method for preparing cerium oxide-based electrolyte powder containing sintering aids, which is similar to Example 1, except that no complexing agent and dispersant are added.
[0061] Performance testing The cerium oxide-based electrolyte powders containing sintering aids prepared in Examples 1 to 5 and Comparative Example 1 were subjected to performance tests, including density and conductivity. The results are shown in Table 1. The XRD pattern of Example 1 is shown below. Figure 1 As shown, the SEM image of Example 1 before ball milling is as follows: Figure 2 (1) shows the SEM image of Example 1 after ball milling. Figure 2 (2) As shown, the conductivity diagram of Example 1 is as follows. Figure 3 As shown.
[0062] The cerium oxide-based electrolyte powder containing sintering aids prepared in Examples 1 to 5 and Comparative Example 1 was granulated by adding 25% wt of PVA aqueous solution (concentration 3% wt). After granulation, the powder was placed in a steel mold and dry-pressed under a pressure of 300 MPa. After demolding, it was placed in a box furnace and calcined at 1000~1400℃ (interval of 100℃) for 4 h to obtain ceramic sheets prepared from cerium oxide-based electrolyte powder containing sintering aids. The true density of the ceramic sheets was measured using Archimedes' displacement method. The ceramic sheets sintered at 1200℃ were used as test objects. Silver paste was uniformly coated on both sides as electrodes, and two silver wires were fixed on the silver electrodes on each side as conductors. The prepared test samples were placed in a tube furnace and heated to 800℃ in an air atmosphere, and then held at that temperature for 30 h. To ensure the thermal stability of the sample, a silver wire was connected using an electrochemical workstation. The electrochemical impedance spectroscopy (EIS) spectrum of the electrolyte sheet was then tested using the four-probe method. This method yielded the ionic conductivity of the ceramic sheet containing cerium oxide-based electrolyte powder with sintering aids.
[0063] Table 6 Performance of cerium oxide-based electrolyte powder containing sintering aids in Examples 1 to 5 and Comparative Example 1
[0064] As shown in Table 6, the true density and relative density of the ceramic sheets containing cerium oxide-based electrolyte powder with sintering aid prepared in Examples 1 to 5 first increased and then remained basically unchanged with the increase of sintering temperature, and the relative density was extremely high. This indicates that the ceramic sheets containing cerium oxide-based electrolyte powder with sintering aid prepared in Examples 1 to 5 can be sintered to a dense state at around 1200℃. This shows that the change in solid content has no effect on the performance of the cerium oxide-based electrolyte powder containing sintering aid prepared in this invention.
[0065] Comparative Example 1, due to the absence of complexing and dispersing agents, exhibited lower density upon sintering at 1200℃ and required 1400℃ to achieve dense sintering. The poor conductivity test results indicate that, without the addition of complexing and dispersing agents, the sintering aids could not be effectively dispersed in the cerium oxide-based electrolyte powder.
[0066] Table 7 Performance of cerium oxide-based electrolyte powders containing sintering aids in Examples 6 to 20
[0067] Depend on Figure 1 It can be seen that the diffraction peaks of the cerium oxide-based electrolyte powder containing sintering aid prepared in Example 1, after sampling from three different positions (top, middle, and bottom), are completely consistent with the standard PDF of 10GDC (10 mol gadolinium-doped cerium oxide) powder, with no impurity phases. This indicates that a small amount of ferric nitrate sintering aid was uniformly mixed with 10GDC and did not accumulate in large quantities locally.
[0068] Depend on Figure 2 (1) Before ball milling and Figure 2 (2) After ball milling, it can be seen that the cerium oxide-based electrolyte powder containing sintering aid prepared in Example 1 has a particle size of about 30 nm before and after ball milling, and the morphology is spherical. This indicates that the ball milling treatment does not affect the primary particle size and morphology of the powder material.
[0069] Depend on Figure 3 It can be seen that the resistivity of the cerium oxide-based electrolyte powder containing sintering aid prepared in Example 1 is 11.3 Ω·cm at 800℃, and the converted conductivity is 0.088 S / cm. The test results are in line with the normal level of 10 GDC materials, indicating that the sintering aid addition method of the present invention does not affect the electrochemical performance of the material while reducing the sintering temperature of the powder material.
[0070] In summary, by adding compounds containing carboxyl, hydroxyl, and amino groups, some of these compounds complex with sintering aid metal ions that are self-soluble in the solvent, while others complex with active sites on the surface of the electrolyte powder. This results in the complexation of carboxyl, hydroxyl, and amino groups with the sintering aid when the first mixture is mixed with the complexing agent. When the second mixture is mixed with the cerium oxide-based electrolyte powder, the carboxyl, hydroxyl, and amino groups in the compounds can also complex with active sites (such as surface hydroxyl groups and surface cerium ions) on the surface of the cerium oxide-based electrolyte powder, thereby fixing the sintering aid on the surface of the cerium oxide-based electrolyte powder. Since the compounds containing carboxyl, hydroxyl, and amino groups are uniformly dispersed in the solution, when mixed with the cerium oxide-based electrolyte powder, the complexing agent that complexes with the sintering aid can also uniformly complex the cerium oxide-based electrolyte powder, thus achieving uniform dispersion of the sintering aid in the cerium oxide-based electrolyte powder.
[0071] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.
[0072] It should be noted that in this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. In this application, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.
[0073] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A method for preparing cerium oxide-based electrolyte powder containing sintering aids, characterized in that, Includes the following steps: The sintering aid and solvent are mixed to obtain the first mixture; The first mixture is mixed with a complexing agent and a dispersant to obtain a second mixture; The second mixture is mixed with cerium oxide-based electrolyte powder to obtain a third mixture. The third mixture is ball-milled, dried, and sintered to obtain cerium oxide-based electrolyte powder containing sintering aids. The complexing agent includes compounds containing carboxyl, hydroxyl, and amino groups; The dispersant includes hexadecyltrimethylammonium bromide.
2. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that, The compounds containing carboxyl, amino, and hydroxyl groups include at least one of citric acid, EDTA, polyvinyl alcohol, glycine, and oxalic acid.
3. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 2, characterized in that, The complexing agent includes at least one of glycine and citric acid.
4. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that, The molar ratio of sintering aid to complexing agent is 1:(3~5).
5. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that, The cerium oxide-based electrolyte powder accounts for 20% to 60% of the mass of the third mixture.
6. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that, The mass ratio of dispersant to solvent in the third mixture is (1~5):
100.
7. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that, The molar ratio of the sintering aid to the cerium oxide-based electrolyte powder is 1:(80~200).
8. The method for preparing cerium oxide-based electrolyte powder containing sintering aid as described in claim 1, characterized in that: The sintering aid includes at least one selected from soluble iron salts, bismuth salts, cobalt salts, and copper salts; and / or, The solvent includes deionized water.
9. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that: The ball mill rotation speed is 300~500 r / min; and / or, The ball milling time is 6~48 hours; and / or, The drying temperature is 120~180℃; and / or, The drying time is 6 to 24 hours.
10. The method for preparing cerium oxide-based electrolyte powder containing sintering aids as described in claim 1, characterized in that... : The sintering temperature is 550~650℃; and / or, The sintering time is 1 to 3 hours.
Citation Information
Patent Citations
Method for synthesizing electrolyte powder of solid oxide fuel cell based on complexing freeze-drying method
CN112490475A
Low-temperature sintering densified samarium-neodymium doped cerium oxide-based barrier layer, preparation method thereof and solid oxide fuel cell
CN114725461A
Solid oxide fuel cell and preparation method and application thereof
CN118825347A
Ceria-based composition, ceria-based composite electrolyte powder, method for sintering the same and sintered body made thereof
US20130189605A1
Method for producing a cerium-gadolinium oxide powder, in particular intended for the production of an electrolyte
WO2024194200A1